Lack of service (in Chilean law) - Agüero San Juan, Claudio Antonio (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
This paper presents a synthesis of meaning of the phrase «lack of service» in Chilean Administrative Law between 1976 and 2002. In first instance, it is argued that this expression designated the French translation of the locution faute de service done by Chilean legislation. On the other hand, it designated two interpretative theses on national normative dispositions that were created by Chilean jurists: i) a local or idiosyncratic thesis defined the expression as a hypothesis of objective responsibility for the absence of a public service, and ii) a thesis defended the idea that it was a legal transplant and defined the expression as a hypothesis of subjective responsibility or negligence of the service according to its use in France.